Carbon and climate efficient use of biogenic carbons in solid waste for circular chemicals through gasification - Mola Mendoza, Marina (My University, 2024)
Municipal Solid Waste (MSW) generation is a growing global concern, aggravated by rapid urbanization, population growth, and industrialization. Annually, approximately 2.1 billion metric tons of MSW are generated, with the trend expected to rise. To address this urgent challenge, solutions must include both capacity increase and MSW treatment sustainability, like converting the non-recyclable waste into chemicals like methanol via gasification. This can potentially reduce the dependence on fossil-based raw materials in the chemical industry, increasing the circularity of the carbon in waste streams. This study explores the feasibility of using gasification for chemical synthesis from MSW, focusing on the Bubbling Fluidized Bed (BFB) gasifier. Moreover, it includes the development of a comprehensive Aspen Plus model to simulate the MSW-to-methanol process for a feedstock input of 100 MWth. It includes drying, gasification, syngas cleaning, syngas conditioning, methanol synthesis loop, and methanol purification stages. The auto-thermal gasification system is modelled using steam as gasifying agent, with a steam-to-feedstock (S/F) ratio of 0.8, and oxygen from an Air Separation Unit (ASU) to combust the volatile matter in the feedstock. In this model, the MSW input is converted into 16.31 tonnes/h of syngas in the gasifier operating at 920 °C, requiring an oxygen flow of 2.12 kg/s from the ASU for the volatiles combustion to sustain the autothermal operation. After the cleaning stage, the syngas has an energy content of 15.31 MJ/kg on a LHV basis. Then, the ratio of H2/CO in the syngas is adjusted to 2.5 via a Water Gas Shift reactor before entering the chemical synthesis loop. In the medium pressure vapor phase reactor, operating at 220 °C with a Cu/Zn/Al/Zr catalyst bed, the syngas is converted into methanol. After distillation, 9500 kg/h of methanol is produced with a molar purity of 99.3%. The overall process energy efficiency is 0.45 and the carbon conversion efficiency is 0.41, meaning that 41% of the biogenic carbon in the MSW is converted into the carbon contained in the methanol product. The techno-economic analysis reveals promising financial indicators, including a payback period of 5 years, a high NPV (276.28 M€), and a competitive levelized cost of methanol of 414.92 €/tonne, suggesting that the proposed process can be economically viable and competitive with current methanol production methods.
Keywords: Municipal Solid Waste; Gasification; Bubbling Fluidized Bed; Syngas; Water Gas Shift; Methanol; technoeconomic analysis